The Influence of Fashion Involvement, Shopping Lifestyle, and Live Streaming Shopping on E-Impulse Buying Fashion Products - Sawitri Sawitri; Awliya Afwa (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2026)
This study aims to analyze the influence of fashion involvement, shopping lifestyle, and live streaming shopping on e-impulse buying of fashion products in TikTok Shop users in Pekanbaru City. The phenomenon of increasing impulse purchases in the context of social commerce is a major concern, especially as TikTok has evolved from a mere entertainment platform to an interactive marketing medium that encourages spontaneous purchase decisions. A quantitative approach was used for the survey method of 100 respondents selected through purposive sampling technique. Data was collected using questionnaires and analyzed by multiple linear regression through SPSS software. The results of the study show that fashion involvement, shopping lifestyle, and live streaming shopping have a positive and significant effect on e-impulse buying of fashion products at TikTok Shop in the city of Pekanbaru. These findings indicate that the higher the consumer engagement with fashion, the stronger their shopping lifestyle, and the more intense the interactive experience through live streaming, the tendency to make impulse purchases also increases. This research offers practical implications for online businesspeople in designing marketing strategies that harness the power of real-time interaction and visual appeal to drive spontaneous purchase decisions.